The accuracy of the heat index to explain the excess of mortality and morbidity during heat waves – a case study in a mediterranean climate - Monteiro, A (2013)
The aim of this contribution was to evaluate the accuracy of a well known human comfort index, the heat index, to anticipate the effects of the July 2006 heat wave in mortality (all causes) and morbidity (all causes, respiratory and circulatory disease). Our assessment was done to all citizens, to people of the 75+ cohort and to each gender, in Porto. For further statistical analysis, we calculated an expected number of admissions by averaging the admissions recorded during the comparison period. The 95% confidence interval was calculated, using a standard method based on the t-distribution, for differences between independent means with different population variances, using the Leveane test to evaluate the variance’s homogeneity. During the 2006 heat wave, a 52% mortality excess was registered relatively to the expected mortality (p < 0.001), for all cohorts of the population. The admissions excess for all ages included the admissions due to respiratory diseases (p < 0.029), pneumonia (p < 0.001) and chronic obstructive pulmonary disease (p < 0.001). For the 75+ cohort, the admissions due to respiratory diseases (p < 0.017), pneumonia (p < 0.001) and heart failure (p < 0.610) were also statistically high. The obtained results confirm that the heat index is a truthful method to anticipate the negative impacts of heat waves in human health even in climate contexts adapted to hot summers like at Porto - a Mediterranean tempered climate. The impacts of July 2006’s heat wave in the increase of mortality (all causes) and in respiratory morbidity (all population and 75+cohort) was evident.